Hierarchical functional system development supports executive function. Issue 2 (February 2023) - Keller, Arielle S.; Sydnor, Valerie J.; Pines, Adam; Fair, Damien A.; Bassett, Dani S.; Satterthwaite, Theodore D.
Abstract: In this perspective, we describe how developmental improvements in youth executive function (EF) are supported by hierarchically organized maturational changes in functional brain systems. We first highlight evidence that functional brain systems are embedded within a hierarchical sensorimotor-association axis of cortical organization. We then review data showing that functional system developmental profiles vary along this axis: systems near the associative end become more functionally segregated, while those in the middle become more integrative. Developmental changes that strengthen the hierarchical organization of the cortex may support EF by facilitating top-down information flow and balancing within- and between-system communication. We propose a central role for attention and frontoparietal control systems in the maturation of healthy EF and suggest that reduced functional system differentiation across the sensorimotor-association axis contributes to transdiagnostic EF deficits. Highlights: Executive function relies on both specialized processing within functional systems and flexible communication between functional systems. Functional systems exhibit graded differences in connectivity profiles that are embedded within a sensorimotor-association axis, a hierarchical axis of cortical organization. Functional systems at the top of this hierarchical axis tend to become more functionally segregated during development, while regions in middle-axis systems become more integrated; this balance may support healthy executive function. Integrative attention and control systems may drive large-scale functional connectome reorganization during late childhood and adolescence, facilitating hierarchical information flow and multisystem coordination. Abnormal functional system development in youth may lead to executive dysfunction, thereby increasing risk for psychopathology.